Effective language teaching for young english learners - Leirerné Katona Ágnes (2001)
Teaching foreign languages has become a very important element of our educational system. Some teachers believe in the importance of teaching languages to very young learners but others find it too early to introduce another languagetosix or seven year old children. In this thesis I will prove that the efficient language teaching for early primary beginners is a real aim of teachers, consequently the period of the oral introductory stage should not be left out from the language teaching and learning process. I will examine all those crucial factors which will help to achieve success in the development of little children's foreign language knowledge. By showing the general characteristics of six to seven year old children, I will prove that this age is very productive and little children are able to learn a foreign language. The efficiency of the process also depends on the well-qualified teachers and I will detail the role of the teacher. I will also examine why the peaceful classroom atmosphere and the good relationship between home and school are so important elements of the teaching and learning process. I will show the importance of a good course book and the conscious planning and through the different types of games, songs and rhymes I will demonstrate the main techniques of playful language teaching and the unique opportunities of this period.